2017
DOI: 10.3892/mco.2017.1329
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography/computed tomography for osseous and soft tissue sarcomas: A systematic review of the literature and meta-analysis

Abstract: Abstract. In order to elucidate the value of positron emission tomography (PET)/computed tomography (CT) in the clinical diagnosis and treatment of osseous and soft tissue malignancies, two authors independently searched the PubMed, Medline, Elsevier, Embase and Cochrane Library databases for literature published between January 2003 and February 2016, using the key words 'PET/CT', 'positron emission tomography/computed tomography', 'osseous sarcoma', 'bone tumor', 'soft tissue sarcoma' and 'neoadjuvant', to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…For this reason, in addition to CT‐scan of the chest for LM screening, lymphnode dissection is mandatory when lymphnode involvement is suspected by diagnostic imaging . For this purpose, positron emission tomography in combination with CT‐scan was proposed as a reliable imaging method …”
Section: Discussionmentioning
confidence: 99%
“…For this reason, in addition to CT‐scan of the chest for LM screening, lymphnode dissection is mandatory when lymphnode involvement is suspected by diagnostic imaging . For this purpose, positron emission tomography in combination with CT‐scan was proposed as a reliable imaging method …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, dedicated FDG-PET was more sensitive in the diagnosis of soft tissue sarcomas. To elucidate the value of PET/CT, Muheremu et al [29] pooled the data of 16 trials and concluded that PET combined with CT is a reliable imaging method to be applied in the diagnosis of osseous and soft tissue malignancies. New diagnostic modalities including PET-MRI combinations have been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…One review found FDG-PET/CT contributed to determining the final causal diagnosis in FUO in 38–75% of cases [8]. In addition, a systematic review examining data from 16 trials found that PET/CT imaging was 90% sensitive and 89% specific for overall diagnostic accuracy in osseous and STSs [9]. However, this imaging modality was not utilized in this case.…”
Section: Discussionmentioning
confidence: 99%